Right to Work and Employment: Exclusion and Disadvantages Experienced by People with Disabilities - Juniar, Mutiah Wenda; Pawennei, Mulyati; Sakharina, Iin Karita; Annisa, Arini Nur (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to find out the exclusions and disadvantages experienced by people with disability in rich and poor countries and to find out whether the obligation of CRPD related to right to work and employment are unrealistically high, lacking in clarity and unlikely to drive helpful reform .This research will evaluate whether rich and poor countries are in the same position where person with disabilities in those two different worlds still experience exclusion and disadvantages and whether the requirements in CRPD to states parties in ensuring the right to work and employment are unrealistically high, lacking in clarity and unlikely to drive helpful reform. In order to obtain the result, the author use literature research method which analyse literatures, regulations and other documents related to the research. This research shows that it is true disabled person both in rich and poor countries still experience disadvantages and exclusion. Mostly, the disadvantages and exclusion that exist in both two different worlds are the lack of regulation about reasonable accommodation, dismissal and discrimination to certain type of disabilities. The obligation to ensure the right to employment and work might be quite complex but not unrealistically high. The unclear provision of reasonable accommodation in CRPD is true but does not mean all the demands regarding employment and work are unclear and does not drives a helpful reform.